Linking a distal ejecta with its source crater: a probabilistic approach applied to tektites - Rochette, Pierre; Baratoux, David; Braucher, Regis; Cornec, Jean; Debaille, Vinciane; Devouard, Bertrand; Gattacceca, Jerome; Gounelle, Matthieu; Jourdan, Fred; Moustard, Fabien; Nomade, Sébastien (Comptes Rendus. Géoscience)
We propose a probabilistic approach to gauge the plausibility of a genetic link between a distal ejecta and a known impact structure, considering the only possible alternative that the distal ejecta could originate from an unknown impact site. We exemplify this approach in the case of three tektite strewn fields related to three known impact structures—the belizites, related to Pantasma (Nicaragua), the ivorites, related to Bosumtwi (Ghana), the moldavites, related to Ries (Germany), as well as on Manson crater ejecta. The computed probability for the unknown meteoritic impact is about 1% or less for these four cases studies.